1998
DOI: 10.1093/nar/26.7.1636
|View full text |Cite
|
Sign up to set email alerts
|

The presence of modified nucleotides is required for cloverleaf folding of a human mitochondrial tRNA

Abstract: Direct sequencing of human mitochondrial tRNALysshows the absence of editing and the occurrence of six modified nucleotides (m1A9, m2G10, Psi27, Psi28 and hypermodified nucleotides at positions U34 and A37). This tRNA folds into the expected cloverleaf, as confirmed by structural probing with nucleases. The solution structure of the corresponding in vitro transcript unexpectedly does not fold into a cloverleaf but into an extended bulged hairpin. This non-canonical fold, established according to the reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
231
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(250 citation statements)
references
References 46 publications
7
231
0
6
Order By: Relevance
“…In addition to the synthesis of phospholipids, SAM is essential for the methylation of various types of nucleic acids present in the mitochondria. In mammals, methylation of DNA, tRNA and rRNA has been documented, and some have been shown to be essential for mitochondrial function [44][45][46][47]. SAM is also necessary for post-translational modifications of some mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the synthesis of phospholipids, SAM is essential for the methylation of various types of nucleic acids present in the mitochondria. In mammals, methylation of DNA, tRNA and rRNA has been documented, and some have been shown to be essential for mitochondrial function [44][45][46][47]. SAM is also necessary for post-translational modifications of some mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that an in vitro transcript of this tRNA does not fold into a functional cloverleaf but into alternative extended bulged hairpins ( Fig. 1A; Helm et al 1998), and is poorly aminoacylated in the presence of a human mt crude enzymatic extract or of an overexpressed and purified mt LysRS (Tolkunova et al 2000). The requirement of a single post-transcriptional modification for cloverleaf folding of tRNA Lys was confirmed by synthesis and structural analysis of a chimeric tRNA Lys , which displays a unique modified base, a methylated adenosine at position 9 ( Fig.…”
Section: Introductionmentioning
confidence: 90%
“…Such variants, carrying an altered base pair at position 50-64 replacing A50-U64 by U50-A64 (Ki) or by G50-C64 (Ke), adopt the expected cloverleaf folding, as demonstrated by enzymatic and chemical probing ( Fig. 1C; Helm et al 1998).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations